The Efektivitas Jet Aerator dalam Pengolahan Limbah Cair Penyamakan Kulit - Vincentia Veni Vera; Anang Lastriyanto; Fajri Anugroho; Adi Sulianto; Wahyunanto Agung Nugroho (Jurnal Ilmu Pertanian Indonesia, 2024)
Finished leather, a primary material for making shoes, bags, and wallets, is processed through tanning to remove veins and feathers. Liquid waste contains a high demand for chemical oxygen (COD), chloride, chromium, and sulfide that can affect river water quality if not treated further. This research was conducted at PT X in Malang City, where liquid waste treatment using an aerator is considered less effective. The tool used in this study is a jet aerator to increase the spread of oxygen in the aeration process. The study aimed to assess changes in the characteristics of tanning liquid waste (pH, temperature, total suspended solids/TSS), and COD) and the effectiveness of using jet aerators in aeration methods in tanning liquid waste treatment. Aeration is carried out for three days. The treatment carried out is aerator + 15 L (A15), jet aerator + 15 L (JA15), and jet aerator + 20 L (JA20). The data were analyzed using Factorial Complete Randomized Design followed by the Smallest Significant Difference test. pH and temperature have met quality standards, while TSS and COD have not. The results showed that the jet aerator +15 L (JA15) decreased maximum tanning liquid waste characteristics on day 1. In contrast, aerator +15 L (A15) and jet aerator +20 L (JA20) decreased maximum waste characteristics on day 2. The jet aerator+15 L (JA15) treatment provides the highest effectiveness value compared to other treatments. COD decreased 49.2%, and TSS decreased 49.7%. Keywords: jet aerator, leather tanning liquid waste